Implementasi Terapi Guided Imagery sebagai Upaya Mengurangi Stres Remaja Menjelang Ujian Sekolah - Salshabila, Jenar Ayu; Apriliyani, Ita; Triana, Noor Yunida (Yayasan Inspirasi El Burhani, 2025)
Introduction: Adolescence is an important developmental phase that is prone to identity crises, emotional instability, and pressure from social and academic environments. Academic stres is one of the main problems that affects mental health, academic achievement, and the quality of life of adolescents. One effective method of coping with stres is guided imagery therapy. Objective: The purpose of this activity is to identify and reduce stres levels among adolescents. Method: The methods used were lectures, discussions, guided imagery therapy demonstrations, pre-tests, and post-tests. The media used were PowerPoint, booklets, LCD, and projectors. The target was ninth-grade students in class C at SMP Negeri 9 Purwokerto. The therapy was conducted three times a week for 10–15 minutes. Result: The results of the study proved effective in reducing students' academic stres. The pre-test results showed that the majority of students experienced moderate stres (82.9%), while the post-test showed a decrease to the mild stres category (68.6%). The average stres score decreased from 44.34% to 36.02%. Statistical analysis using a paired t-test showed a significant difference between pre-test and post-test scores (p < 0.001), confirming the effectiveness of guided imagery therapy in reducing academic stres. Conclusion: Guided imagery has been proven to provide relaxation, reduce academic stres, and can be practiced independently by students.